Political economy of food security in least developed nations: a review - Koirala, Niraj P; Koirala, Dhiroj P (Journal of Agriculture and Environment, 2014)
Conversion of many least developed nations from food exporter to net food importer along with sectoral improvement of other sectors of national economy with international trade liberalization has raised concerns about efficacy of international trade policies to uplift food security condition of such nations. The paper has reviewed literatures emphasizing on political economy of international food and agriculture agreements. Different efforts to restore food security in LDCs are explained together with the logics behind failure of such multinational initiatives to address food insecurity in those nations. Globalization and agrobiodiversity are explained in relevance to food security. The paper concludes that international economic efforts should focus on tackling food insecurity problems with trade policies emphasizing agro-biodiversity promotion in LDCs where majority of citizens are not solvent economically. Similarly, the paper stresses on analysis of food security in LDCs as a sub-component of whole development paradigm in regional and global level.